DISSEMINATED TUBERCULOSIS PRESENTING AS HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS - Kargupta, Arindam; Das, Indrani; Sengupta, Ananya; Chakraborti, Abhishek; Ghosh, Shounak (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Hemophagocytic lymphohistiocytosis (HLH) is an immune dysregulation syndrome which is characterized by widespread but ineffective activation of immune system of our body. This activation leads to release of a large pool of cytokines from the activated lymphocytes and macrophages. This hypercytokinemia leads to the development of characteristic features of HLH such as fever, cytopenias, hepatosplenomegaly, raised serum ferritin level, hemophagocytosis in marrow/spleen/lymph nodes, low fibrinogen and or hypertriglyceridemia, low natural killer cell activity, and high-soluble CD25 [1]. Five out of the above eight features are required for the diagnosis. There are 2 variants of HLH, primary HLH; where the defect in the immune system is hereditary and secondary HLH; where it is caused by other secondary diseases such as infections, hematological malignancies, autoimmune and auto-inflammatory diseases. In this article, we have reported a case of HLH, which was secondary to disseminated tuberculosis. There are only few case reports of HLH secondary to disseminated tuberculosis. Mortality may be as high as 50%. Although tuberculosis has various manifestations, our patient presented with fever, skin rash, cytopenias, splenomegaly, and very high ferritin. Marrow examination showed epithelioid granuloma, hemophagocytosis, and positive Ziehl–Neelsen staining. At present, no definite treatment guidelines have been formulated because of multiple drug interactions and toxicities. We treated our patient with non-hepatotoxic anti-tubercular drugs and steroids, followed by addition of isoniazid, rifampicin, and pyrazinamide on improvement of hepatic profile. Thus, high index of clinical suspicion, prompt diagnosis, and early management may reduce the mortality in this devastating disease. Moreover, this is more common in immunocompromised patients, but here, we have diagnosed this case in an immunocompetent man. Keywords: Erythematous rash, Fever, Disseminated tuberculosis.